School variables and pupil achievement - Guerrero, Carolina S. (1987)
Data on 1440 randomly selected pupils from 40 sample schools in Region 1, National Capital Region and Region 4 were gathered through a questionnaire that disaggregated data on pupil, teacher, and school characteristics. Univariate, bivariate and multivariate data analyses revealed that about 41 percent of the pupil's achievement level is due to the combined effects of all pupil characteristics but more significantly as a result of his: mental ability, grade level, habit of studying at home, ability to concentrate, and overall grade average. About 19 of the pupils level of achievement is due to the combined effects of all teacher characteristics particularly the teachers' perceptions on the pupils, perceptions on the pupils' performance, age, teaching experience, job position as a master/non-master teacher and use of grouping as a teaching strategy. About 11 percent of the pupils level of achievement is due to the combined effects of all school characteristics but more significantly as a result of the variables: Region 1, book per pupil ratio, survival rate and dropout rate.
Thesis (Ed.D.)--University of the Philippines, Diliman.
Typescript.
Keywords: Performance in children; Elementary schools